Exploring the Challenges Faced by Students in Science Learning: Influencing Internal and External Factors - Oktian Fajar Nugroho (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to explore the various challenges faced by students in learning science and to analyze the internal and external factors that influence them. This research is motivated by the low success rate of students in science courses, which is thought to be due to multiple obstacles involving cognitive, affective, and learning environment aspects. The research method used is a qualitative approach, with data collected through in-depth interviews and surveys of students enrolled in science courses at universities. The findings show that internal factors, such as self-efficacy, basic mathematical skills, and intrinsic motivation, play a significant role in influencing students’ understanding of science material. On the other hand, external factors, including curriculum, teaching methods, environmental support, and facility limitations, also have a substantial impact. This study suggests improvements in curriculum reform at the elementary and secondary levels, more interactive teaching methods, and adequate academic support to help students overcome difficulties in science courses. These findings are expected to provide insights for educational institutions and educators in designing more effective learning strategies to enhance students' competencies in science.